Fixação biológica de nitrogênio e aspectos nutricionais em povoamentos de Anadenanthera peregrina var. peregrina E Schizolobium parahyba var. amazonicum em função da densidade de plantio e condições ambientais - Bighi, Kelly Nery (2021)
Monocultures of two legume species widely used in reforestation in Brazil were studied, which have contrasting growth and survival strategies. The planting is part of a large experiment established in the Atlantic Forest where the climate is Aw, with the slow-growing and N2-fixing tree, Anadenanthera peregrina var. peregrina and the fastgrowing, non-fixing species Schizolobium parahyba var. amazonicum. Therefore, 54 plots with the species were evaluated between 44 and 67 months of age in three densities (625; 1111 and 1666 trees ha-1). The study has three objectives: 1) the investigation of N pools and the biological fixation of N in A. peregrina, using a nonfixing species as a reference, and two methods were tested to estimate N fixation; 2) Estimate the nutrient pools and the efficiency of species use of nutrients (EUN); and 3) Explore the relationship between edaphic and topographic characteristics of the study area with the growth of species. The species present divergent patterns of δ15N signature, accumulation of nutrients in the biomass and response to the characteristics of the planting site. The biological fixation of N2 was greater in less densely planted A. peregrina. However, N2 fixation estimates depend on the method used. The fixing species was less affected by intraspecific competition, accumulating more N in the biomass than S. parahyba, in a density of 1111 and 1666 trees ha-1. The accumulation of nutrients is more accentuated in the wood of S. parahyba, except for N and Ca, which accumulate in greater proportions in the leaf and bark, respectively. Estimates indicate that in A. peregrina the largest stock of nutrients is located in the roots, but further studies are needed to corroborate these findings. Among the evaluated nutrients, N, Ca and K had a relatively low EUN when compared to P, Mg and S. An EUN pattern associated with densification was not observed. The density was little related to the nutritional and topographic attributes of the soil. The edaphic characteristics and plant nutrition were the main factors that influenced the growth and production of biomass in A. peregrina. The topography and characteristics of the soil were the main conditioning factors of the dendrometric variation in S. parahyba.